2014
DOI: 10.4161/hv.34300
|View full text |Cite
|
Sign up to set email alerts
|

Moving a Carbohydrate Mimetic Peptide into the clinic

Abstract: Tumor-Associated Carbohydrate Antigens (TACAs) are broad-spectrum targets for immunotherapy. Immunization with Carbohydrate Mimetic Peptides (CMPs) is a strategy to induce broad-spectrum TACA-reactive antibodies hypothesized to interfere with cellular pathways involved in tumor cell survival. A Phase I study was conducted with a first-in-man CMP referred to as P10s, conjugated to the Pan T cell carrier PADRE, along with MONTANIDE(™) ISA 51 VG as adjuvant over a course of 5 immunizations. While designed as a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The ability of these antibodies to bind to TACA and interfere with signalling events also suggest additive or synergistic modality with chemotherapeutics that are cytotoxic. Most importantly, our studies suggested a potential clinical benefit to the combination of TACA-reactive antibodies as illustrated by the multiple antibodies induced with the P10s vaccine in cancer patients [1]. The sensitization of cancer cell via inhibition of cell survival pathways, show for the first time that signalling pathways interrupted by vaccine induced TACA reactive antibodies causes tumor regression in combination with standard of care chemotherapeutics.…”
Section: Commentarymentioning
confidence: 63%
See 3 more Smart Citations
“…The ability of these antibodies to bind to TACA and interfere with signalling events also suggest additive or synergistic modality with chemotherapeutics that are cytotoxic. Most importantly, our studies suggested a potential clinical benefit to the combination of TACA-reactive antibodies as illustrated by the multiple antibodies induced with the P10s vaccine in cancer patients [1]. The sensitization of cancer cell via inhibition of cell survival pathways, show for the first time that signalling pathways interrupted by vaccine induced TACA reactive antibodies causes tumor regression in combination with standard of care chemotherapeutics.…”
Section: Commentarymentioning
confidence: 63%
“…Our observation that P10s immunization enhances reactivity to the ganglioside GD2 and LeY in humans is one example of inducing responses to multiple TACAs with a pan-immunogen, which has therapeutic ramifications such as driving epitope spreading. In our early phase clinical trial we observed some direct clinical benefit in one of our subjects with metastatic lesions as evaluated before and after vaccine treatment [1]. Inducing antibodies to multiple TACA can contribute to overcome immune-escape mechanisms since TACA are always expressed on tumor cells which increases the therapeutic potential of this cancer vaccine.…”
Section: Commentarymentioning
confidence: 85%
See 2 more Smart Citations
“…MCF-7 cells are known to have a dysfunctional caspase 3, [ 36 ] and a lack of growth-inhibitory activity could be due to caspase-3 deficiency in this cell line. Our previously published data [ 37 ], through testing for Annexin V-FITC/PI on serum-treated MDA-MB-231 cells, implicated apoptosis in P10s-induced antibody-mediated growth inhibition. If the induction of apoptosis is caspase-3-dependent, then apoptotic antibodies do not affect cells deficient in caspase-3 activity.…”
Section: Resultsmentioning
confidence: 99%